Prospective Investigation of the Operating Room Time-Out Process. (March 2020) - Freundlich, Robert E.; Bulka, Catherine M.; Wanderer, Jonathan P.; Rothman, Brian S.; Sandberg, Warren S.; Ehrenfeld, Jesse M.
Abstract : BACKGROUND: Although the surgical pause or time-out is a required part of most hospitals' standard operating procedures, little is known about the quality of execution of the time-out in routine clinical practice. An interactive electronic time-out was implemented to increase surgical team compliance with the time-out procedure and to improve communication among team members in the operating room. We sought to identify nonroutine events that occur during the time-out procedure in the operating room, including distractions and interruptions, deviations from protocol, and the problem-solving strategies used by operating room team members to mitigate them. METHODS: Direct observations of surgical time-outs were performed on 166 nonemergent surgeries in 2016. For each time-out, the observers recorded compliance with each step, any nonroutine events that may have occurred, and whether any operating room team members were distracted. RESULTS: The time-out procedure was performed before the first incision in 100% of cases. An announcement was made to indicate the start of the time-out procedure in 163 of 166 observed surgeries. Most observed time-outs were completed in <1 minute. Most time-outs were completed without interruption (92.8%). The most common reason for an interruption was to verify patient information. Ten time-out procedures were stopped due to a safety concern. At least 1 member of the operating room team was actively distracted in 10.2% of the time-out procedures observed. CONCLUSIONS: Compliance with preincision time-outs is high at our institution, and nonroutine events are a rare occurrence. It is common for ≥1 member of the operating room team to be actively distracted during time-out procedures, even though most time-outs are completed in under 1 minute. Despite distractions, there were no wrong-site or wrong-person surgeries reported at our hospital during the study period. We conclude that the simple act of performing a preprocedure checklist may be completed quickly, but that distractions are common.